Non-invasive prenatal testing: MeDIP-PCR to detect trisomy 21 from maternal plasma - Abdul Ghafar, Nurul Fatehah; Muhammad, Siti Aesah @ Naznin; A. Talib, Norlelawati; Roslani, Anna Liza; Ismail, Rozihan; Zainuddin, Norafiza (2019)
Introduction: Down syndrome is a predominant genetic disease with an incident rate of one in every 750 live births. This abnormality can be identified through non-invasive and invasive procedures. Currently, the use of cell-free fetal DNA (cfDNA) from maternal plasma is widely implemented as one of the alternatives for non-invasive prenatal screening. However, due to the high cost, the test is mainly offered in private healthcare settings. Aim: The aim of this study was to verify the reliability of using methylated DNA immunoprecipitation (MeDIP) on fetal DNA for trisomy 21 detection. Methods: cfDNA was isolated from 21 pregnant women, consisted of 19 normal and two confirmed trisomy 21 pregnancies. The extracted cfDNAs were fragmented, immunoprecipitated and quantified by real-time qPCR for three specific methylation markers or differentially methylated region (DMR) at chromosome 21. Then, the methylation ratio values of the normal and trisomy 21 cases for each DMR were compared to assess the level of discrimination of the markers. The Mann-Whitney U test was used to determine the statistical significance of each DMR. Results: No clear separation was found between normal and trisomy cases using all three DMRs. Discussion and conclusion: MeDIP methods have been adopted into our study based on its reported sensitivity and specificity, with slight modifications. However, the results indicated that the markers or DMRs were unable to discriminate the status of our samples (either normal or trisomy 21) which might be attributed to the insufficient number of trisomy 21 samples. Hence, a larger number of cases were necessary to verify and validate this approach.